Efektivitas Penggunaan Model Pembelajaran JigsawTerhadap Pemahaman Siswa Pada Materi Mata Pencaharian Penduduk Mata Pelajaran IPS KelasVII SMP Negeri 1 Klego Tahun Ajaran 2015/2016 - Ahmad, Mahfuddin; , Dra. Siti Taurat Aly,M.Pd (2017)
The research was done in SMP Negeri 1 KlegoBoyolali. The purpose of this peelitian is to assess and describe: 1. The jigsaw strategy is more effective in achieving the learning objectives sub theme of livelihood. 2. The difference in learning strategy and learning conventional jigsaw. This study trmasuk types eksperien method that is research by studying an objective, systematic. Place of research conducted in SMP Negeri 1 KlegoBoyolali, Waku research for one day starting at 07:30 until 10:45 on 27 May 2016 poplasinya taken two classes, namely class E and F class VII SMP Negeri 1 Klego Boyolai. Independent and dependent variables of the study. Data collection techniques there are 2 of tests and observation. Technical analysis is no validity, rebilits, normalita. No hypothesis analysis techniques to determine the level of student understanding. The conclusion of this study (1) jigsaw strategy is more effective in achieving the learning objectives at the sub-themes of livelihood. (2) The jigsaw strategy has better results than the conventional methods (lectures), although only slightly, but perbandunganya jigsaw strategy is more effective than conventional methods.